Technologies in creative economy and creative society - Kačerauskas, Tomas (Technological and Economic Development of Economy, 2015)
The article deals with issues of technologies in the environment of creative economy and creative society, mostly focusing on the following topics: 1) invasion of technologies, which is accompanied by technical illiteracy or simplification of intellection presupposed by a certain technique (e.g. computers); 2) new technologies emerge in the environment dominated by consumption in order to boost consumption; 3) political, media and communication technologies are intertwined to the extent that allows us to speak about the technologized society; 4) technologies are inseparable from creative activities: on the one hand, development of technologies needs creativity, on the other hand, every branch of creative industries needs certain technologies; 5) technologic development is conditioned by their syncretism, i.e. their ability to serve the art (technē) of life and creative intentions; 6) in the creative society, happiness does not depend on constantly upgraded (i.e. consumed) technologies but is rather possible in spite of them; 7) unlimitedness is the greatest limitation of global technologies: unconnected with any existential region, they billow in the wind of ever newer technologies.First published online: 29 May 2015